Reconciliation of cattle ranching with biodiversity and social inclusion objectives in large private properties in Paraguay and collective indigenous lands in Bolivia. (September 2020) - Painter, Lilian; Nallar, Rodolfo; Fleytas, Maria del Carmen; Loayza, Oscar; Reinaga, Ariel; Villalba, Laura
Abstract: Livestock ranching is one of the most important economic activities of the planet but is also associated with negative environmental impacts. Ranching can also exacerbate social inequality by displacing vulnerable rural populations from access to land and decisions over land use. The large-scale ranching typical of the Paraguayan Chaco, and the small scale ranching typical of northwestern Bolivia, represent two contrasting cases of livestock expansion in Latin America. These two distinct contexts are used to evaluate best practices for sustainable ranching at different scales. In particular, how ranching practices can contribute to achieving the Sustainable Development Goals. Technical assistance was provided to both the large private ranchers as well as to the indigenous communities focusing on pasture cultivation and management, recovery of native pastures, rotational grazing, improved fire management through the use of burn calendars and no burn zones. The success of these interventions in reducing forest loss was measured by evaluating the increase in carrying capacity, considered synonymous with stocking rates in Paraguay and hrough measurement of above green matter. Success in improving animal health and reproductive output was monitored through interviews and periodic blood and fecal sample analysis. Interviews were also carried out to evaluate mitigation of conflicts between carnivores and livestock. The impact of interventions to promote participation and equity was evaluated using complementarity of planning instruments with indigenous territorial plans and indigenous population size. Intensification of agricultural production, this is increasing productivity rates through more efficient gazing management per unit of land already in use as an alternative to horizontal land use expansion, helped reduce forest loss both in areas managed by large private ranchers as well as those managed by small scale indigenous ranchers, and contributed to the achievement of SDG 15. In the case of Paraguay improved ranching practices that minimize environmental impacts while increasing profitability of production, have enabled positive results for conservation but, the limited progress in the recognition of indigenous territorial rights and more recent development of territorial planning capacity at the municipal level are obstacles to achieving greater co-benefits for social equity (SDG 10). Indigenous territorial rights and territorial management capacity in the Leco and T'simane Mosetene indigenous lands reduce inequality (SDG 10) by empowering indigenous small-scale ranchers, and securing their equal access to land and natural resources. Clear land allowed them to implement conservation and sustainable ranching plans leading to improved productivity relevant for SDG 2 and also enabled them to leverage respect and support for their territorial management vision from protected area and municipal authorities. The impact of improved ranching practices with large private ranchers resulted in greater impacts on the reduction of forest loss (SDG 15) but impacts on social inclusion (SDG 10) were only achieved in Bolivia due to the existence of indigenous territorial capacity. Highlights: Ranching practices can be improved to achieve the sustainable development goals. Improved pasture management contributed to SDG 15 and SDG2. Indigenous land rights and participatory planning contributed to SDG10.